2007
DOI: 10.1105/tpc.106.046011
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Light and Clock Modulation of Cytosolic Free Ca2+ Oscillations and RhythmicCHLOROPHYLL A/B BINDING PROTEIN2Promoter Activity inArabidopsis

Abstract: Plants have circadian oscillations in the concentration of cytosolic free calcium ([Ca 2þ ] cyt ] cyt and CAB2 promoter activity are uncoupled in the timing of cab1 (toc1-1) mutant but not in toc1-2. We suggest that the circadian oscillations of [Ca 2þ ] cyt and CAB2 promoter activity are regulated by distinct oscillators with similar components that are used in a different manner and that these oscillators may be located in different cell types in Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 76 publications
(138 reference statements)
4
93
0
Order By: Relevance
“…However, it is also possible that the genes assessed ( CCR2 and LHY ) and mutant backgrounds ( toc1‐4 and toc1‐10 ) used contribute to the anomaly; toc1‐4 is a null mutant in Col with a stop codon close to the N‐terminus (Para et al ., 2007), while toc1‐10 in Ws has a large deletion after S255 (Locke et al ., 2006). Similarly, toc1‐2 affects the period of both CAB2 promoter activity and cytosolic Ca 2+ rhythms, whereas toc1‐1 only affects CAB2 promoter activity (Xu et al ., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the genes assessed ( CCR2 and LHY ) and mutant backgrounds ( toc1‐4 and toc1‐10 ) used contribute to the anomaly; toc1‐4 is a null mutant in Col with a stop codon close to the N‐terminus (Para et al ., 2007), while toc1‐10 in Ws has a large deletion after S255 (Locke et al ., 2006). Similarly, toc1‐2 affects the period of both CAB2 promoter activity and cytosolic Ca 2+ rhythms, whereas toc1‐1 only affects CAB2 promoter activity (Xu et al ., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of tissue-specific circadian behavior; for example, the vascular bundle circadian clock appears to have a different genetic architecture compared with other tissues (Para et al, 2007). We previously reported that in the timing of chlorophyll a/b binding protein expression1-1 mutant the circadian rhythms of [Ca 2+ ] cyt become uncoupled from those of CHLOROPHYLL A/B BINDING PROTEIN2 expression, demonstrating the presence of at least two circadian oscillators running at different speeds (Xu et al, 2007). We speculated that these different circadian oscillators might be located in different cell types (Xu et al, 2007).…”
Section: Localization Of Nycthemeral and Circadian Oscillations Of [Cmentioning
confidence: 99%
“…The daily oscillations of [Ca 2+ ] cyt peak at around 300 nM about 8 h after dawn (Love et al, 2004). The circadian clock and PHYTOCHROME A-, CRYPTOCHROME1-, and CRYPTOCHROME2-dependent signaling pathways drive daily rhythms of [Ca 2+ ] cyt (Dalchau et al, 2010) with cyclic ADP ribose (cADPR) acting as an intermediary Xu et al, 2007).…”
Section: Camentioning
confidence: 99%
See 1 more Smart Citation
“…7 On the other hand, the mutant toc1-2 has short period of both rhythms of CAB2 promoter activity and circadian [Ca 2+ ] cyt oscillations (~21 h). 1,7 This allele has a base pair change that results in changes to preferential mRNA splicing, resulting in a truncated protein with only 59 residues. 7 Thus, the mutated CCT domain in toc1-1 might lead to the uncoupling of rhythms of CAB2 promoter activity and circadian [Ca 2+ ] cyt oscillations while the absence of TOC1 in toc1-2 causes the shortening of the period of both rhythms.…”
mentioning
confidence: 99%